Comprehensive Review Of Organizational Design And Structure - Manikam, Amar Mutiara Ahsin; Astuti, Tyas Ayu Septi; Nur, Mila Dyah; Halimah, Rizska Nur; Sijabat, Rauly (Maroon Journal De Management, 2025)
Organizational structure and design are the main foundations in carrying out activities and achieving organizational goals effectively. Organizational structure regulates the formal relationship between tasks and authorities, while organizational design represents how the structure is formed and adjusted to the internal and external needs of the organization. In a dynamic era, organizations are required to adapt through an open system approach that prioritizes interaction with the environment. This study examines key elements in organizational structure such as work specialization, departmentalization, chain of command, span of control, centralization-decentralization, and formalization. In addition, factors that influence organizational design-including strategy, scale, technology, and environment-are also analyzed. Various structural models such as simple, functional, product, matrix, and network structures are explained along with their advantages and challenges. Understanding the theory of organizational structure and culture enriches the perspective on how organizational design plays a role in supporting performance and adaptation amidst rapid environmental changes. This study provides a theoretical and practical basis for the development of adaptive and effective organizational structures.